Anelastic spectroscopy in SmBa2Cu3O7 - Grandini, Carlos Roberto [UNESP]; Gimenez, JMD; da Cunha, A. G. (Elsevier B.V., 2004)
The possibility of variable stoichiometry and the high mobility of oxygen in the CuOx planes of SmBa2Cu3O7 give rise to a rich phase diagram. Measurements of the elastic energy loss and modulus (anelastic spectroscopy) as a function of temperature can distinguish among the different atomic jumps, which occur in the various phases or at different local ordering. In this paper, it is reported anelastic relaxation measurements in SmBa2Cu3O7, above room temperature, using a torsion pendulum operating in frequencies around 40 Hz. The mobility of oxygen atoms in the CuOx planes in the various phases has been discussed and the thermally activated peak of elastic energy dissipation observed around 500 K was interpreted in that framework. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: SmBaCuO; anelastic spectroscopy; oxygen mobility; cuprates